DEVELOPING DOMINO CARDS AS VOCABULARY MEDIA IN LEARNING NOTICE FOR THE SEVENTH GRADE STUDENTS AT SMP NEGERI 1 SIDIKALANG - Ratni Sari Padang; Anni Holila Pulungan; Ade Aini Nuran (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2019)
This research was aimed to develop domino cards as the students’ vocabulary media in leaning notice for grade 7 students of SMP Negeri 1 Sidikalang. This study was categorized as Research and Development (R & D) study which adapted from Borg and Gall (2003). The method through six phases: conducting need analysis, designing, developing, experts validating, revising, and implementing. The subjects of this research were 32 students of grade seventh of SMPN 1Sidikalang which was located in Jl. Diponegoro No. 1 Sidikalang. The data and data resources were the teacher’s lesson plan, teacher’s interview, and students’ questionnaires result. After getting the last data, the media should be planned to be designed as the students’ needs. The media were developed and had been validated by the experts. The percentages of the media from the experts were 90% that categorized as very good. It can be concluded that domino cards gave many benefits for the students, such as improve their vocabulary, made them enjoy studying English, get easier in learning notice after using needed media. The media were also eligible to use as media because it gave clear instruction to use it.Key words:Research and development (R&D), Students’ Vocabulary Media, notice, Domino Cards,Junior High School..